Clinical spectrum of infants with thiamine responsive pulmonary arterial hypertension - Uppalapati, Tanmayi; Krishna, Yathirajam S.; Eregowda, Adarsh (International Journal of Contemporary Pediatrics, 2023)
Pulmonary arterial hypertension (PAH) is a progressive disorder caused by hypertension in blood vessels from heart to lungs. Exclusively breastfed infants are at the highest risk due to their high metabolic demand and low thiamine level in mothers. Symptoms are observed to be sometimes precipitated with the presence of co morbidity such as sepsis and lower respiratory tract infections. This study explains 10 cases with varied clinical presentation and response to management of different grades of infantile pulmonary arterial hypertension.